Deleuze and Rawls: philosophical-political convergences and divergences - Fernández, Luis Diego (ARFIL y UNL, 2021)
The aim of this article is to analyze the texts and interventions of Gilles Deleuze from 1979-1980 onwards from certain concepts such as “Social Democratic State”, “Becoming-democratic”, “Becoming-minor” and “Jurisprudence” in order to evaluate the hypothesis of a liberal-progressive reading of its political philosophy in its mature period. We will inquire about the convergences and divergences of the Deleuze position with certain notions of John Rawls, such as “Political Liberalism”, “Property-Owning Democracy”, “Liberal Socialism”, “Overlapping Consensus”, “Reasonable Pluralism” and “Public Opinion” in order to question the potential affinity between the political philosophies of both thinkers.